Colloquial Cambodian the complete course for beginners - Sak-Humphry, Chhany (Colloquial series., 2016)
"Colloquial Cambodian provides a step-by-step course in Cambodian as it is written and spoken today. This new edition has been developed by a linguist and an experienced Cambodian language professor and combines an accessible approach with a thorough treatment of the language, equipping learners with the essential skills needed to communicate confidently and effectively in Cambodian in a broad range of situations. No prior knowledge of the language is required"--Provided by publisher.